THE USE OF THE WORD TABOO ON SOCIAL MEDIA: A FORENSIC LINGUISTIC STUDY - Surya Kelana Putra; Eddy Setia; Syahron Lubis; Gustianingsih Gustianingsih (Institut Pendidikan Tapanuli Selatan, 2023)
The freedom in social media communication have not been responded wisely by the citizen of the net (netizen). Sometimes while expressing themselves in the social media, netizens used the taboo words which potentially break the law. The problems chosen in this research is a type of taboo words used by the netizen and also whether these expressed words have a potential to violate the law. The method to collect the data is “Simak bebas libat cakap“(SBLC), it is a method where there is no active communication between interviewer and interviewee but it is only taken the data from internet, then to transcribe the taken data. The following step is analyzing data which used referential equivalent method, then the results of the analysis were presented informally. The findings showed that taboo words used in social media consisted of: (1) obscene words, (2) vulgar language, and (3) nick name and insult. These taboo words potentially violate the government regulation of the Republic Indonesia number 11 of 2008 concerning electronic information and transactions article 27 paragraph (3) and article 45 paragraph (1) as well as article 310 section (1) and article 311 section (1) of the Indonesian Criminal Code concerning defamation. Therefore, netizens must be careful in the way how communicate.